The Effect of Formative Assessment Assisted by Artificial Intelligence on Students' Essay Writing Skills at UMMY Solok - Mega Putri; Yenni Rozimela; Syahrul Ramadhan (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The development of Artificial Intelligence (AI) has created new opportunities for implementing formative assessment in higher education, including writing instruction. However, empirical research examining the effect of AI-assisted formative assessment on essay writing skills among students in Indonesian language education remains limited. This study aims to analyze the effect of AI-assisted formative assessment on the essay writing skills of students in the Indonesian Language Education Study Program at Mahaputra Muhammad Yamin University (UMMY) Solok. A quantitative approach with a quasi-experimental method and a nonequivalent control group design was employed. The sample consisted of 40 students, comprising 20 students in the experimental group and 20 students in the control group. The experimental group received AI-assisted formative assessment, whereas the control group received conventional formative assessment. Data were collected using an essay writing test assessed based on five aspects: content, organization, vocabulary, language use, and writing mechanics. The data were analyzed using descriptive statistics, normality tests, homogeneity tests, paired sample t-tests, independent sample t-tests, and effect size analysis using Cohen’s d. The findings show that the average post-test score of the experimental group was higher than that of the control group. The independent sample t-test produced a Sig. (2-tailed) value of 0.020 (< 0.05), indicating a significant difference between the two groups. The effect size analysis yielded a Cohen’s d value of 0.77, categorized as medium to high. In addition, improvement in the experimental group occurred across all assessment aspects, with the highest gains found in content and language use. This study concludes that AI-assisted formative assessment has a significant effect on students’ essay writing skills. The findings contribute to the development of technology-enhanced formative assessment in writing instruction and provide practical implications for using AI as a supporting tool to improve academic writing quality through fast, specific, and continuous feedback.